Sinnlichkeit und Vernunft in der mittelalterlichen Musiktheorie - Hentschel, Frank (Stuttgart Steiner, 2000)
Any form of theoretical examination of music must deal with the problem of how sensual experience is conceptualised. Inspired methodologically by Thomas S. Kuhn, the author examines this problem from an interdisciplinary, historical perspective using the examplAny form of theoretical examination of music must deal with the problem of how sensual experience is conceptualised. Inspired methodologically by Thomas S. Kuhn, the author examines this problem from an interdisciplinary, historical perspective using the example of medieval music theory from the environment of the University of Paris around 1300. The starting point is the analysis of valuation strategies underlying the order of consonances. Since medieval musica theorica was considered a mathematical science, i.e. a philosophical discipline, the descriptions often lead into the history of philosophy and science. (Transalted with Deepl.com)
Keywords: Middle Ages (500-1400); Music theory